Research on the restorative effects and perception of privacy driven activities in Chinese classical gardens—Case studies of three Suzhou gardens - Liu, Hanxin; Bin, Guoshu; Wang, Xiao; Luo, Jia; Liu, Minyi (Frontiers in Public Health, 2024)
The need for privacy, as a fundamental human psychological need, has gained increasing recognition and attention as researchers start examining the restorative effects of privacy driven activities (PDA). This study conducts quantitative experiments and analyses to examine the restorativeness of PDA in three Chinese classical gardens, revealing the advantage of such PDA over typical leisure activities regarding emotional recovery, stress reduction, and attention restoration. It identifies five key factor dimensions that influence the occurrence of PDA through the identification of preferred locations and behavioral preferences the in three gardens. Further regression analysis reveals notable differences in the impacts of these five environmental feature dimensions on the evaluation indicators of"preference for privacy-oriented activities" and "restorative effects". Among these dimensions, "spatial scale and accessibility" has the greatest impact on the"preference for privacy-oriented environments", while "spatial atmosphere" and "activity facilities" have the most significant impact on "restorative effects". Therefore, a location's spatial scale must be properly arranged, and its spatial accessibility enhanced, to attract visitors; attention should also be given to the spatial privacy atmosphere, the sense of security, and the quantity and arrangement of activity facilities to ensure satisfactory restorative effects. The findings will benefit further studies on PDA's restorative pathway.